2018
DOI: 10.1016/j.cell.2018.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Epigenetic Crosstalk as a Therapeutic Strategy for EZH2-Aberrant Solid Tumors

Abstract: Mutations or aberrant upregulation of EZH2 occur frequently in human cancers, yet clinical benefits of EZH2 inhibitor (EZH2i) remain unsatisfactory and limited to certain hematological malignancies. We profile global posttranslational histone modification changes across a large panel of cancer cell lines with various sensitivities to EZH2i. We report here oncogenic transcriptional reprogramming mediated by MLL1's interaction with the p300/CBP complex, which directs H3K27me loss to reciprocal H3K27ac gain and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
134
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(147 citation statements)
references
References 49 publications
13
134
0
Order By: Relevance
“…Because BRD4 and EZH2 each potently promotes IH, as demonstrated by our conditional knockout and gene transfer in vivo experiments presented herein, this BRD4/EZH2 axis is mechanistically important. In support of our finding, enhanced efficacy of combined BETs and EZH2 inhibitors has been reported in cancer research 32 . Moreover, a recent report showed that BRD4 regulated EZH2 expression by indirectly upregulating c-myc in cancer cells 19 , although it was not addressed as to whether epigenetic mechanisms were involved.…”
Section: Discussionsupporting
confidence: 91%
“…Because BRD4 and EZH2 each potently promotes IH, as demonstrated by our conditional knockout and gene transfer in vivo experiments presented herein, this BRD4/EZH2 axis is mechanistically important. In support of our finding, enhanced efficacy of combined BETs and EZH2 inhibitors has been reported in cancer research 32 . Moreover, a recent report showed that BRD4 regulated EZH2 expression by indirectly upregulating c-myc in cancer cells 19 , although it was not addressed as to whether epigenetic mechanisms were involved.…”
Section: Discussionsupporting
confidence: 91%
“…A recent report demonstrated that MLL1 expression level and H3K27ac upregulation are positively correlation with resistance to EZH2 inhibition (39). In agreement with the report, our results showed that the cells that were sensitive to BR-001 expressed low level of MLL-1, whereas BR-001-resistant cells had relative high level of MLL-1 and H3K27Ac (Fig.…”
Section: Resistance To Br-001 Is Associated With H3k27 Acetylationsupporting
confidence: 93%
“…Differential response to EZH2 small-molecule inhibitors like EI1 and GSK126 were observed in GC B cell lymphoma cell lines, owing to the activation of IGF-1R, MEK, and PI3K pathways [145], MLL1-P300/CBP-directed H3K27 acetylation gain [146] as well as secondary EZH2 mutations in wild-type and mutant EZH2 alleles [147,148].…”
Section: Ezh2 Inhibitorsmentioning
confidence: 99%